Aspects of the reproductive biology, movements and site fidelity of right whales off Australia - R. Burnell, Stephen (J. Cetacean Res. Manage., 2020)
Between 1991 and 1997 right whales were studied on their wintering grounds on the southern coastline of Australia, predominantly at the Head of the Great Australian Bight, where over 350 individuals have been identified. The observed mean inter-calf interval for females was 3.33±0.10 years (±SE, n = 57) at the Head of the Bight and 3.64±0.13 years (±SE, n = 117) in the wider Australian population. When inter-calf intervals of six or more years were excluded, the mean intervals became 3.28±0.09 years (±SE, n = 56) and 3.28±0.06 years (±SE, n = 107), respectively. Inter-calf intervals of two years were recorded following the early death of a neonate on two separate occasions and the implications of these ‘shortened’ intervals and of calvings that were not observed are discussed. The mean age at which yearlings were observed to be fully weaned was calculated to be 365±8 days (±SE, n = 18) from the estimated birth dates of individual calves and subsequent associations, or lack of them, between the yearlings and their cows the following year. A total of 108 movements greater than 200km in length were made by individual whales. The mean within-year movement was 730±84 km, made over 34±4 days (±SE, n = 18), whilst the mean between-year movement was 1,036±45km (±SE, n = 87), made over a mean interval of 3.3±0.3 years (±SE, n = 90). The number and direction of coastal movements observed suggest that the right whales off southern Australia comprise a single population which may undertake an almost circular, anti-clockwise migration to the south of the Australian continent. A significantly greater proportion of females displayed a level of between-year fidelity to the Head of the Bight aggregation area (92%, n = 61) than did males (68%, n = 19) or whales of unknown sex (63%, n = 8).